Profil Psikologis Anak Pascabencana: Gambaran Tingkat Kecemasan pada Remaja Penyintas Bencana Banjir dan Tanah Longsor - Sumarti Endah Purnamaningsih; Iswanti Purwaningsih; Dhiya Urrahman; Agus Setiyawan; Teuku Tahlil; Marthoenis (Jurnal Indonesia Sehat, 2026)
Background: Indonesia is one of the countries most vulnerable to natural disasters, with landslides frequently causing physical destruction and psychological consequences among affected populations. Adolescents are particularly susceptible to mental health problems following disasters due to their developmental stage and limited coping capacity. Anxiety is one of the most common psychological responses that may interfere with emotional well-being, social functioning, and academic performance. Objective: To describe the anxiety profile among adolescents following a landslide disaster at a junior high school in Aceh Tamiang Regency. Methods: This study employed a quantitative descriptive design with a cross-sectional approach. A total of 539 students were recruited using total sampling. Anxiety was assessed using the Screen for Child Anxiety Related Emotional Disorders (SCARED) questionnaire consisting of 41 items. Data were analyzed using SPSS software and presented as descriptive statistics, including frequencies and percentages. Results: Most respondents were female (55.41%), had experienced evacuation (85.45%), reported moderate to severe housing damage (73.13%), and had lost family members due to the disaster (80.41%). Overall, 70.32% of the students were identified as having anxiety. Separation anxiety was the most prevalent anxiety dimension (78.29%), followed by panic disorder/somatic symptoms (51.58%), generalized anxiety (43.23%), social anxiety (41.37%), and school avoidance (36.36%). Conclusion: The majority of adolescents affected by the landslide disaster were identified as experiencing anxiety, with separation anxiety representing the most prominent psychological problem. Implication: These findings highlight the importance of early mental health screening and school-based psychosocial support as part of psychiatric nursing services to identify adolescents at risk of anxiety and promote psychological recovery following disasters.